Persepsi Konsumen terhadap Bauran Pemasaran Produk Roti Holland Bakery Boulevard di Kota Manado - Missy J. Nonutu; Charles Ngangi; Yolanda P.I. Rori; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTMissy Juwita Nonutu. The Consumer Perception of Bread Product’s about the Marketing Mix at Holland Bakery Boulevard in Manado City. Under guidance of Charles R.Ngangi as chairman, and Yolanda P.I. Rori and Ellen G. Tangkere as members.The objective of this research is to describe the bread product consument’s perception about the marketing mix (based on the product, price, place and promotion) at Holland Bakery Boulevard in Manado City The method used in this research is survey method. This research uses primary and secondary data. Sampling method used in this research is accidental sampling. Primary data are obtained from interviewed with respondent, which is consumens who buy bread products at Holland Bakery Boulevard, with total of 60 consumens as respondents, using questioner to collect the data. Secondary data are obtained from interviewed with the manager of Holland Bakery Boulevard. Data analysis used in this research is descriptive which analized with Likert Scale and presented in table form.This research result shows that based on product, the highest level index of consuments perception was at product’s flavour indicator. Based on price, the highest level index of consuments perception was at the compatibilty beetwen price and the product’s quality indicator. Based on location, the highest level index of consuments perception was at the indicator of location, comfortability and cleanliness of outlet. Based on promotion, the highest level index of consuments perception was at the publication efectivity indicator. Promotion efectivity indicator is have the lowest level index of consuments perception, which was classified as sufficients, were as the other indicator was classified as good. Generally, based on likert scale analysis showed that the bread product consument’s perception about the marketing mix at Holland Bakery Boulevard was classified as good.